Impact of nanomaterials on sustainable pretreatment of lignocellulosic biomass for biofuels production: An advanced approach - Srivastava N.; Singh R.; Srivastava M.; Mohammad A.; Harakeh S.; Pratap Singh R.; Pal D.B.; Haque S.; Tayeb H.H.; Moulay M.; Kumar Gupta V. (My University, 2025)
Biomass to biofuels production technology appears to be one of the most sustainable strategies among various renewable energy resources. Herein, pretreatment is an unavoidable and key step to increase free cellulose availability and digestibility to produce green fuels. Various existing pretreatment technologies of lignocellulosics biomasses (LCBs) face distinct challenges e.g., energy consuming, cost intensive, may lead partial removal of lignin, complex inhibitors production as well as may cause environmental pollutions. These, limitations may be overcome with the application of nanomaterials, employed as nanocatalysts during the pretreatment process of LCBs. In this prospect, the present review focuses and summarizes results of numerous studies and exploring the utilizations of magnetic, carbon based nanostructure, and nanophotocatalysts mediated pretreatment processes along with their possible mechanisms to improve the biofuels production compared to conventional chemical based pretreatment approaches. Furthermore, different aspects of nanomaterials based pretreatment methods with their shortcomings and future prospects have been discussed. © 2022 Elsevier Ltd